2005
DOI: 10.2113/176.4.343
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual modelling of sand bars morphodynamics for a microtidal beach (Sète, France)

Abstract: The sandy littoral of Sète, with its barred shoreface, is one of the three studied sites of the thematic action “Morphodynamics of sandy beaches” of the French Programme National d’Environnement Côtier (PNEC), selected because of its microtidal wave-dominated characteristics and of the long time series of available data. During the PNEC program, the principal results obtained show that the morphological evolution of the sedimentary bars can be synthesized according to two conceptual models, in reaction to hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 24 publications
3
25
0
2
Order By: Relevance
“…5). These types of morphologies are not unusual in the Mediterranean, as they were reported by Certain and Barusseau (2005) at Lido de Sete, on the Languedoc French coast. In this case the authors call them "sinuous" bars, but possibly the original French term "en-echelon" better describes them (R. Certain, personal communication).…”
Section: The Morphodynamic Visual Classificationsupporting
confidence: 78%
See 2 more Smart Citations
“…5). These types of morphologies are not unusual in the Mediterranean, as they were reported by Certain and Barusseau (2005) at Lido de Sete, on the Languedoc French coast. In this case the authors call them "sinuous" bars, but possibly the original French term "en-echelon" better describes them (R. Certain, personal communication).…”
Section: The Morphodynamic Visual Classificationsupporting
confidence: 78%
“…Certain and Barusseau (2005) already discussed in detail this aspect and the reader can find in their paper alternative models to NOM. From a study of a Mediterranean beach at Lido de Sete (France), the authors propose in addition to the NOM behaviour a model of Oscillation around a Position of Equilibrium (OPE) as usual behaviour for the bars, while they suggest that a NOM behaviour is only triggered by extreme storm events (return period 20-50 years).…”
Section: Changes In the Position Of The Bar Crestmentioning
confidence: 99%
See 1 more Smart Citation
“…It differs considerably for Noordwijk (The Netherlands) where crescentic features of the outer bar had a lifetime of 0.5-37months (Van Enckevort and Ruessink, 2003). Certain and Barusseau (2005) also showed that a decadal storm was required to straighten the outer bar at the microtidal Sètes Beach. Truc Vert Beach outer bar lifetime may be of the same order as the latest as crescentic patterns deduced from breakers were still clearly observed on an aerial photograph during high energy conditions with H s ≈ 6 m (Castelle, 2004), suggesting Hs on the order of 10 m (i.e.…”
Section: Truc Vert Beach State Modelmentioning
confidence: 91%
“…During peak storm phases, an important offshore migration of the bars with a change in shape and a shoreline retreat are observed. During waning episodes, bar reshaping is observed due to onshore sediment transport (Certain and Barusseau, 2005). Between storm events, the wave amplitude is almost constant with a low mean significant height (0 b H s b 1 m) and a peak period ranging from 7 to 10 s. These calm weather intervals have no significant impact on the bottom evolution.…”
Section: Wave Forcing Scenariimentioning
confidence: 99%